(untitled) (LACCEI, 2024)
The paint industry at the level of Mypes, concentrates various critical processes in the production process. This is because they lack a planning and engineering support system, which trigger problems such as: low on-time delivery rate, defective products, stock breaks, among others. Based on this, the case study that is 24% below the standard regarding on-time deliveries is presented. To do this, a production model of Standard Work and Raw Material Management is proposed in a painting Mype in Peru. The diagnosis is given through an analysis of times and activities that includes the manufacture of paints, as well as the analysis of production stops regarding the shortage of raw material. The model will be applied under a hybrid model of implementation and simulation. Through this, it is possible to optimize the production cycle time by 33.6% (301.13 min to 225.39 min) and, therefore, increase production capacity by 13.51% (1377 gallons/shift to 1563 gallons/shift). Likewise, stock out decreases from 6.52% to 0.22% and on time deliveries (On Time Delivery indicator) present an improvement of 17.85%.